IN SEARCH OF OBJECTIVITY: D.H. LAWRENCE’S MINING NARRATIVES AS A REFLECTION OF INDUSTRIAL STRUGGLES - Mohan, Chander (ShodhKosh: Journal of Visual and Performing Arts, 2024)
D.H. Lawrence’s works often delve deeply into the psychological and social implications of modern industrial life, with particular attention to its dehumanizing effects on the working class. Among his most evocative stories are those set against the backdrop of the mining industry, a sector that held significant sway over the industrial revolution in Britain. This paper explores Lawrence’s mining narratives within the framework of objectivity, seeking to examine how his stories both reflect and critique the economic and emotional struggles of the industrial working class. Drawing upon a close reading of Lawrence's short stories such as The Rocking-Horse Winner, The White Peacock, and Odour of Chrysanthemums, the paper argues that Lawrence uses these narratives not only to critique the mining industry and industrialization but also to explore the inherent contradictions of objectivity in portraying class struggles. Through this analysis, the paper highlights how Lawrence’s attempt at objective storytelling often intersects with personal emotional and moral concerns, complicating his portrayal of industrial life and class divisions